Innovative technologies based management of the training process of female athletes specializing in short distances running - Karaulova, S.; Boychenko, K.; Malikov, N.; Bogdanovskaya, N.; Samolenko, T.; Apaychev, A.; Korobeynikova, L. (Journal of Physical Education and Sport, 2018)
Purpose: optimization of the training process` management system for the female athletes aged 19-23 years, specializing in short-distance running, using innovative technologies. Material: analysis and generalization of scientific and methodological literature, sequential pedagogical experiment, testing of physical performance, aerobic capabilities, functional preparedness, methods of mathematical statistics. 8 elite female athletes specializing in short-distance running aged 19-23 were examined Results: determined specific aspects of the dynamics of indicators of the functional preparedness of the female athletes' bodies in the preparatory period of the final macro-cycle of training. Developed an experimental program for the training process planning for improving of the female athletes` preparedness in preparation for the XXX Summer Olympic Games in London. Conclusions: the obtained results indicated that introduction of this program into the preparatory period training process, taking into account the aspects of the dynamics of the female athletes' functional preparedness components and the nature of their correlation with the model characteristics, contributed to significant improvement in all indicators of the functional preparedness of examined female athletes. At the end of the preparatory period, deviations of these indicators from the model values amounted to only 2-6%. Demonstrated effectiveness of the innovative computer program use in the training process` management system, which contributed to getting the new quality information through the primary data processing, based on which the Ukrainian national track and field team coaching staff has made their optimal managerial decisions.